Literatura polska w świetle komparatystyki rumuńskiej - Constantin Geambaşu (Postscriptum Polonistyczne)
The author analyzes the contribution of the Romanian Polonists to studying Polish literature on the basis of theories and methodologies that are characteristic of comparative studies, developed within the Romanian area (T. Vianu, Al. Dima, G. Calinescu, N. Manolescu). Thanks to the comparative method, Romanian specialists have extended their interpreting perspective by voicing original ideas on motifs, themes, influences, parallelisms etc. that are present in the works of Polish and Romanian writers. Special attention has been granted to comparative studies about Mickiewicz – Asachi, Sienkiewicz – Sadoveanu, Reymont – Rebreanu. In conclusion, the comparative method becomes a basic tool in the critical approach of foreign Polonists.